2006
DOI: 10.1111/j.1365-3040.2006.01499.x
|View full text |Cite
|
Sign up to set email alerts
|

Complex adjustments of photosynthetic potentials and internal diffusion conductance to current and previous light availabilities and leaf age in Mediterranean evergreen species Quercus ilex

Abstract: The increases in diffusion limitations in older leaves and at higher light scaled with age-and light-dependent increases in M A and D F . Overall, our study demonstrates a large potential of foliage photosynthetic acclimation to changes in leaf light environment, but also highlights enhanced structural diffusion limitations in older leaves that result from leaf structural acclimation to previous rather than to current light environment and accumulation of structural compounds with leaf age.

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
3
1
1

Citation Types

20
155
6
1

Year Published

2009
2009
2021
2021

Publication Types

Select...
5
3
1

Relationship

0
9

Authors

Journals

citations
Cited by 157 publications
(184 citation statements)
references
References 80 publications
(225 reference statements)
20
155
6
1
Order By: Relevance
“…Leaves of trees in a higher planting density usually suffer from lower light irradiance from the shading of among branches (Warren et al 2001). In this study, the lower g m in the high planting density was consistent with that found in previous studies (Piel et al 2002;Niinemets et al 2006;Flexas et al 2007;Warren et al 2007). In addition to g m , the decrease in the photosynthetic rate was usually caused by Table 3 The gas exchange parameters, chlorophyll pigment contents, and leaf Each value is the mean±SE (n=8).…”
Section: Discussionsupporting
confidence: 82%
See 1 more Smart Citation
“…Leaves of trees in a higher planting density usually suffer from lower light irradiance from the shading of among branches (Warren et al 2001). In this study, the lower g m in the high planting density was consistent with that found in previous studies (Piel et al 2002;Niinemets et al 2006;Flexas et al 2007;Warren et al 2007). In addition to g m , the decrease in the photosynthetic rate was usually caused by Table 3 The gas exchange parameters, chlorophyll pigment contents, and leaf Each value is the mean±SE (n=8).…”
Section: Discussionsupporting
confidence: 82%
“…Additionally, we found a low photosynthetic level at high densities, with nevertheless a relatively high C i , suggesting that the stomatal conductance was not the main limitation on photosynthesis (Tuzet et al 2003). Relative to the stomatal conductance, the mesophyll conductance was more sensitive to changes in the surroundings, such as shading (Niinemets et al 2006;Warren et al 2007;Flexas et al 2007Flexas et al , 2008 and drought (Duan et al 2009). Leaves of trees in a higher planting density usually suffer from lower light irradiance from the shading of among branches (Warren et al 2001).…”
Section: Discussionmentioning
confidence: 83%
“…Increasing needle tissue density has lowered CO 2 concentration in intercellular spaces and probably increases mesophyll resistance to CO 2 that leads to a reduction of PNUE with A. alba needle age (Niinemets et al 2005(Niinemets et al , 2006. The other authors showed that mesophyll (internal) conductance to CO 2 (g i ) was correlated with the surface area of chloroplasts exposed to intercellular air space and g i decreased with leaf age which might also be expected in our study tree (Hanba et al 2001;Miyazawa and Terashima 2001).…”
Section: Discussionsupporting
confidence: 64%
“…The C i cut-off point was determined based on the method proposed by Ethier et al (2006). This method has been successfully used in several studies, showing a good agreement with other independent estimates of g m (Niinemets et al, 2006). Detailed and thorough evaluation of errors resulting from assuming an infinite g m when fitting the Farquhar et al (1980) model equations to A-C i curves are given in Ethier and Livingston (2004).…”
Section: Gas-exchange Measurements and Estimation Of Mesophyll Conducmentioning
confidence: 99%